Evaluation of Dimethyl Sulfoxide and Dexamethasone on Pulmonary Contusion in Experimental Blunt Thoracic Trauma - Boybeyi, Ozlem; Bakar, Bulent; Aslan, Mustafa Kemal; Atasoy, Pinar; Kisa, Ucler; Soyer, Tutku (The Thoracic and Cardiovascular Surgeon, 2014)
Background A thoracic trauma model was designed to evaluate the effect of dimethyl sulfoxide (DMSO) and dexamethasone (DX) on histopathologic and oxidative changes in lung parenchyma seen after pulmonary contusion.Methods Twenty-four Wistar albino rats were included in the study. They were allocated into control (CG, n = 6), sham (SG, n = 6), DX (DXG, n = 6), and DMSO (DMG, n = 6) groups. Only a lung biopsy was performed in CG. In the experimental groups, blunt thoracic trauma was induced by dropping a cylindrical metal weight (0.5 kg) through a stainless steel tube onto the right hemithorax from a height of 0.4 m (E = 1.96 J). In the SG, 1 mL of physiologic saline was injected intraperitoneally, in the DXG 10 mg/kg of DX was injected intraperitoneally, and in the DMG 1.2 g/mL of DMSO was injected intraperitoneally 15 minutes after trauma. After 6 hours, lung biopsy was performed for histopathologic and oxidative injury markers.Results Histopathologically, congestion, hemorrhage, neutrophil infiltration, endothelial-nitric oxide synthase (E-NoS), and total pathologic score were significantly higher in SG, DXG, and DMG when compared with CG (p < 0.05). Neutrophil infiltration, total pathologic score, and E-NoS were significantly decreased in DMG when compared with SG and DXG (p < 0.05). Biochemically, superoxide dismutase (SOD) level was significantly higher in SG, DXG, and DMG than in CG. SOD level was significantly lower in DXG and DMG than in SG (p < 0.05).Conclusion DMSO prevents further injury by decreasing neutrophil infiltration and endothelial injury in lung contusions. DX may have a role in the progression of inflammation but not in preventing the pathologic disruption of pulmonary parenchyma.
Keywords: dimethyl sulfoxide; dexamethasone; experimental; chest; lung; trauma